Potential utilization of oil shale as a stabilizing material for compressed Earth block - Al-Fhaid, Hamza; Edris, Walid Fouad; Al-Tamimi, Mahmoud (Frontiers in Built Environment, 2023)
This research aims to produce a Compressed Earth Block (CEB) product locally from soil collected from north Jordan. The CEB mixture was further stabilized using Oil Shale (OS) and ordinary Portland Cement (OPC). CEB specimens were thoroughly characterized by studying the mechanical properties (compressive and flexural strength) and durability characteristics (erosion, absorption, and shrinkage tests). eight mixtures were carried out for CEB. One of these mixtures is the control mix, in addition to other mixtures that were carried out by replacing soil with OS, cement, and sand in different proportions. The results showed that the higher compressive strength and flexural strength for CEB were obtained in the mixtures which contained 10% of OS and 10 % of cement. The absorption was increased when the OS increased in the soil. The consequence erosion test is related to the absorption test, where the higher the absorption, the negative results of the erosion test. Moreover, oil shale improved the shrinkage properties of the CEB, as the higher the proportion of oil shale in the CEB, the lower the shrinkage.